Increasing vaccine acceptance using evidence-based approaches and policies: Insights from research on behavioural and social determinants presented at the 7th Annual Vaccine Acceptance Meeting. (April 2021) - Attwell, Katie; Betsch, Cornelia; Dubé, Eve; Sivelä, Jonas; Gagneur, Arnaud; Suggs, L. Suzanne; Picot, Valentina; Thomson, Angus
Highlights: The World Health Organisation has flagged vaccine hesitancy as one of the top 10 threats to global health. Vaccine acceptance is influenced by various social and practical factors. More vaccine hesitancy studies are needed in low- and middle-income countries. Educating children about vaccination could avoid future vaccine hesitancy. Training in effective communication is needed for healthcare professionals. Abstract: Background: In 2019, the World Health Organization (WHO) flagged vaccine hesitancy as one of the top 10 threats to global health. The drivers of and barriers to under-vaccination include logistics (access to and awareness of affordable vaccines), as well as a complex mix of psychological, social, political, and cultural factors. Increasing vaccine uptake: There is a need for effective strategies to increase vaccine uptake in various settings, based on the best available evidence. Fortunately, the field of vaccine acceptance research is growing rapidly with the development, implementation, and evaluation of diverse measurement tools, as well as interventions to address the challenging range of drivers of and barriers to vaccine acceptance. Annual Vaccine Acceptance Meetings: Since 2011, the Mérieux Foundation has hosted Annual Vaccine Acceptance Meetings in Annecy, France that have fostered an informal community of practice on vaccination confidence and vaccine uptake. Mutual learning and sharing of knowledge has resulted directly in multiple initiatives and research projects. This article reports the discussions from the 7th Annual Vaccine Acceptance Meeting held September 23–25, 2019. During this meeting, participants discussed emergent vaccine acceptance challenges and evidence-informed ways of addressing them in a programme that included sessions on vaccine mandates, vaccine acceptance and demand, training on vaccine acceptance, and frameworks for resilience of vaccination programmes.